Answer:
the vertices are all labeled
a b c d and e
Answer:
9 years ( approximately)
Step-by-step explanation:
900(1.03)^t = 1200
(1.03)^t= 1.33
( 1.03)^t= ( 1.03)^9
So, t= 9
as you may already know, to get the inverse of any expression, we start off by doing a quick switcheroo on the variables, and then solve for "y".
![\bf \stackrel{f(x)}{y}=x^3-9\implies \stackrel{\textit{quick switcheroo}}{\underline{x}=\underline{y}^3-9}\implies x+9=y^3\implies \sqrt[3]{x+9}=\stackrel{f^{-1}(x)}{y}](https://tex.z-dn.net/?f=%5Cbf%20%5Cstackrel%7Bf%28x%29%7D%7By%7D%3Dx%5E3-9%5Cimplies%20%5Cstackrel%7B%5Ctextit%7Bquick%20switcheroo%7D%7D%7B%5Cunderline%7Bx%7D%3D%5Cunderline%7By%7D%5E3-9%7D%5Cimplies%20x%2B9%3Dy%5E3%5Cimplies%20%5Csqrt%5B3%5D%7Bx%2B9%7D%3D%5Cstackrel%7Bf%5E%7B-1%7D%28x%29%7D%7By%7D)
<span>statements is not true
</span><span>D. -a = c
-a should be equal d, not c</span>
Google it. ('>')...................................................